2004
DOI: 10.4322/rbcv.2014.347
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos níveis de aglutininas antileptospira em cães de caça na Paraíba, Brasil

Abstract: ResumoDentre os animais domésticos, em nível urbano, os cães representam a principal fonte de infecção da leptospirose humana, pois vivem em contato direto com o homem e uma vez infectados podem eliminar leptospiras vivas através da urina durante meses, mesmo sem apresentar sinais clínicos da doença. Particularmente, os cães de caça constituem animais de companhia que são utilizados por adeptos da atividade esportiva de caça à procura de espécies silvestres no meio rural, sendo esta uma prática comum em várias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…The Autumnalis serogroup was the second most prevalent, and although it is considered uncommon in dogs, in recent years there has been an increase in seropositivity reports (Lemos et al 2010, Castro et al 2011, 2015. It is worth mentioning that among domestic species, this serogroup is more frequently reported as predominant in sheep (Alves et al 2004, Higino et al 2010, Barbante et al 2014) and goat (Araújo Neto et al 2010, Pimenta et al 2019. Therefore, it is likely that sheep and goat may be acting as reservoirs for this serogroup, thus contaminating the environment and other species, including dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Autumnalis serogroup was the second most prevalent, and although it is considered uncommon in dogs, in recent years there has been an increase in seropositivity reports (Lemos et al 2010, Castro et al 2011, 2015. It is worth mentioning that among domestic species, this serogroup is more frequently reported as predominant in sheep (Alves et al 2004, Higino et al 2010, Barbante et al 2014) and goat (Araújo Neto et al 2010, Pimenta et al 2019. Therefore, it is likely that sheep and goat may be acting as reservoirs for this serogroup, thus contaminating the environment and other species, including dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of the disease is influenced by several factors, including geographic distribution and socioeconomic factors (Baquero & Machado 2018), and in this context the conduction of epidemiological surveys in different locations is important. Some surveys with dogs have been carried out in the state of Paraíba (Alves et al 2004, Batista et al 2004, Azevedo et al 2011, Silva et al 2017b, Brasil et al 2018, Fernandes et al 2018a, however, there are still no surveys that indicate the epidemiological situation of canine leptospirosis in the Brejo paraibano microregion, which can be considered a important transmission area, as this region presents specific characteristics that may influence the occurrence of this disease, including the presence of remnants of the Atlantic Rainforest (Porto et al 2004) and high rainfall (AESA 2019). According to data from the Ministry of Health, 325 cases of human leptospirosis from 2000 to 2018 were confirmed in the state of Paraíba (SINAN 2017), which reinforces the need to carry out epidemiological surveys in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Another aspect that increases the risk of infection is the practice of hunting wild animals, which exposes dogs and humans to contaminated environments. Alves et al (2004) found a leptospirosis frequency of 8.95% (17/190) in hunting dogs in Paraíba. Lastly, the peculiar situation regarding the period of intense drought should be considered, which may have favored the approach of animals, especially wild animals, to the peridomicile in search of water and food, thus causing the contamination of the environment through urine.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is possible that the serotypes found are related to the occurrence of these hosts in the environment, as most respondents (139/184) reported the presence of these rodents on their properties, and 42/184 hunted wild animals. Alves et al (2004) found that 8.95% (17/190) of hunting dogs in the state of Paraíba tested positive for anti-Leptospira agglutinins. The most frequently detected serotype was Autumnalis, suggesting involvement of wild animals in the transmission cycle of the disease.…”
Section: Discussionmentioning
confidence: 99%